2010
DOI: 10.1037/a0019692
|View full text |Cite
|
Sign up to set email alerts
|

Suicidal, abused African American women's response to a culturally informed intervention.

Abstract: Findings highlight the value of incorporating Nia as an adjunctive intervention for abused, suicidal, low-income women. They underscore the ways the intervention needs to be bolstered to address more directly more mediating and moderating constructs, as well as the need to target more effectively the key outcomes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
91
1
3

Year Published

2013
2013
2020
2020

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 162 publications
(96 citation statements)
references
References 55 publications
1
91
1
3
Order By: Relevance
“…Our sample of African-American females had a mean age of 35.59 years old (SD = 11.43; see Table 1) and were recruited as part of a larger IRB-approved intervention study (Kaslow et al, 2010). We attempted to enrol all African-American women presenting to the hospital emergency Notes: Depressive symptoms = BDI-second edition total score, excluding Item 9; daily hassles = survey of recent life events total and subscale scores; religious and existential well-being = SWBS subscale scores; suicidal ideation = BSS ideation total score.…”
Section: Methods Proceduresmentioning
confidence: 99%
“…Our sample of African-American females had a mean age of 35.59 years old (SD = 11.43; see Table 1) and were recruited as part of a larger IRB-approved intervention study (Kaslow et al, 2010). We attempted to enrol all African-American women presenting to the hospital emergency Notes: Depressive symptoms = BDI-second edition total score, excluding Item 9; daily hassles = survey of recent life events total and subscale scores; religious and existential well-being = SWBS subscale scores; suicidal ideation = BSS ideation total score.…”
Section: Methods Proceduresmentioning
confidence: 99%
“…Cox and Stoltenberg's (1991) research on groups labeled as psychoeducational-only found mixed results with self-esteem improving on one model but not assertiveness or locus of control in the other. A psychoeducational group specific to African American women (Kaslow et al 2010) found significant improvements on depression and general distress but not PTSD symptoms or suicidal ideation. With respect to groups described as primarily supportive, Tutty et al (1993) reported statistical improvements on self-esteem, belonging support, locus of control, less traditional attitudes towards marriage and the family, perceived stress, and marital functioning.…”
Section: Group Intervention With Abused Womenmentioning
confidence: 95%
“…Four reports only briefly stated in the results section [29], methods section [30,31] or the discussion [32] that no adverse events occurred or were observed, without providing information about how these adverse events were defined or monitored.…”
Section: Accepted M Manuscriptmentioning
confidence: 99%